CHARACTERIZATION IN CLASSICAL TEXTS - Sevara Baratova Musoxonovna (International Journal of Literature and Language Studies, 2026)
The article analyzes the epithets found in the texts of the mathnawi “Sabot al-Ajizin” and “Rohati Dil” from a linguopoetic point of view. Constant and individual adjectives revealing the writer’s skill are compared. It is proved that epithets serve to create metaphors.